1965
DOI: 10.1126/science.150.3705.1837
|View full text |Cite
|
Sign up to set email alerts
|

Photopic Spectral Sensitivity in the Monkey: Methods for Determining, and Initial Results

Abstract: Data were obtained on the spectral sensitivity of the light-adapted monkey by two operant conditioning techniques adapted to use with brief duration stimuli: cued avoidance conditioning, and a positive reinforcement-reaction time method. The results are compared with human photopic spectral sensitivity, and detailed similarities are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1965
1965
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…This result is consistent with target sizes used in studies in which rhesus long wavelength sensitivity was suppressed relative to the human (9,10,(16)(17)(18). In other rhesus and human comparisons of photopic spectral sensitivity, much more agreement exists between human and rhesus in the spectral sensitivity range from 580 to 640 nm (6)(7)(8). However, all of these studies utilized test targets many times larger than the test target limits which we used for observing rhesus long wavelength insensitivity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This result is consistent with target sizes used in studies in which rhesus long wavelength sensitivity was suppressed relative to the human (9,10,(16)(17)(18). In other rhesus and human comparisons of photopic spectral sensitivity, much more agreement exists between human and rhesus in the spectral sensitivity range from 580 to 640 nm (6)(7)(8). However, all of these studies utilized test targets many times larger than the test target limits which we used for observing rhesus long wavelength insensitivity.…”
Section: Discussionsupporting
confidence: 79%
“…However, all of these studies utilized test targets many times larger than the test target limits which we used for observing rhesus long wavelength insensitivity. Yet, in at least two studies (7,8) a small deficit in rhesus long wavelength sensitivity either appeared without comment or was noted and dismissed as incidental experimental variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors, using different techniques, have measured the photopic spectral sensitivity of various species of Cercopithecoidea (Grether, 1939;Sidley, Sperling, Bedarf & Hiss, 1965;Schrier & Blough, 1966;Sidley & Sperling, 1967;Behar & Bock, 1974;De Valois, Morgan, Polson, Mead & Hull, 1974;Zwick & Robbins, 1978). Because different procedures are known to affect the shape of luminosity curves (Borstein & Marks, 1973), it is not unexpected that these studies have reported curves of somewhat different shapes.…”
Section: Comparisons With Psychophysical Datamentioning
confidence: 99%
“…Finally, it should be pointed out that the present results are quite similar to those previously reported for this species by Jones, Polson, and DeValois (1964), using ERG measures. is difficult to compare the present results with those of Sidley, Sperling, Bedarf, and Hiss (1965). However, there 'ire discontinuities in the individual photopic functions that suggest secondary peaks corresponding 422 btes…”
Section: Photopic Functionmentioning
confidence: 52%